Structure–energy relationship of food materials using differential scanning calorimetry - Saadi, Sami; Ariffin, Abdul Azis; Mohd Ghazali, Hasanah; Saari, Nazamid; Mohammed, Abdulkarim Sabo; Anwar, Farooq; Hamid, Azizah Abdul; Nacer, Nor Elhouda (Wiley, 2023)
The use of differential scanning calorimetry (DSC) in the food authentication and process-chain traceability has raised significant amelioration in terms of structure and stability of some structured foods. In this review article DSC is used to raise other quantitative energy parameters related to structural reconformation and variation in the intra-molecular dimension of studied materials. These properties are explained by the respective energy models involving (1) quantum energy, (2) quantum mass, and (3) quantum velocity. These models parameters are explored as well as on from enthalpy, entropy, heat capacity, and Gibbs free energy of transition in determining the nucleation energy relevant to crystallization and polymorphic transformation of some studied food-materials. Practical Application: Differential scanning calorimetry is remaining the powerful thermoanalytical tool used in studying the mechanism of crystallization, polymorphism, and structural reconformation of biological matters. The expression of energetic parameters on from enthalpy, entropy, heat capacity, and Gibbs free energy of transition help in determining the nucleation energy whether is stable or in the meta-static forms. In addition these energy parameters are the key elements in understanding whether the food materials undergoing denaturation, unfolding or reversible folding, meaning that DSC is able in determining the status of food materials whether is stable or instable as well as the texture whether is soft, grainy, or coarse and also the polymorphic forms of the crystals and stability of the emulsions. Thus, gathering information on the thermal analysis using DSC helped in establishing some model correlation between energy and structure in association with the chemical composition changes of some model of oils and fats.